The history, science and preliminary results from the reintroduction of the Chequered Skipper, Carterocephalus palaemon into Rockingham Forest, England - N. A. D. Bourn; S. O’Riordan; D. Maes; P. Goffart; T. Shadbolt; L. Hordley; A. W. Sainsbury; C. Bulman; D. Hoare; R. Field; J. Curson; J. P. Wildman; et al. (Journal of Insect Conservation, 2024)
Habitat loss and fragmentation have caused declines in the abundance and distribution of butterflies, particularly habitat specialists. The Chequered Skipper, Carterocephalus palaemon , has been extinct in England since 1976 after declining from the 1940s predominantly due to changes in woodland management including afforestation and the decline in traditional coppice management. To enable C. palaemon to flourish again, this species was reintroduced from Belgium to England in 2018 with the aim of establishing a resident breeding population. Here, we report on the recent reintroduction, outlining the reintroduction method used, the establishment status of the species in England, the clinical health of reintroduced individuals, and post-release monitoring results. Furthermore, we assess the habitat suitability of sites around the original release site to determine which were similar to the current re-location site and could be used for future reintroductions, and to aid the targeting of further management to increase habitat suitability. Since 2018, 128 Chequered Skipper butterflies have been reintroduced from Belgium to Rockingham Forest in England. Health examinations demonstrated that individuals were healthy, and this in part resulted in the population establishing at the first release site and the area of occupancy increasing each year to 2022. However, the reintroduced population has yet to naturally colonise other areas within Rockingham Forest and therefore is not yet a functioning metapopulation. Despite the project still being in its infancy, we are able to report on a successful five years. Implications for insect conservation: Rigorous scientific research has provided the evidence to support reintroductions, and will continue to be used to ensure the ecology and population dynamics of this species is sufficiently understood so that Chequered Skipper populations can thrive again in England.